HUBUNGAN PERSAHABATAN DAN KONSEP DIRI PADA REMAJA PUTRI - Amaliyah, Hanifah (Batanang : Jurnal Psikologi, 2025)
This article explains in general about the friendship relationship between young women with the self-concept that exists in individuals. Adolescence is a time when individuals seek identity and the formation of self-concept. Many factors influence a personÔÇÖs self-concept. One of the factors that influence self-concept is relationships with other people. Teenagers get this influence from the relationships they have with their peers. Positive friendship will form a positive self-concept.